Designing User Interface and User Experience by Using User Centered Design on Gamified Platform "Ezedu" - Priyantini, Dwi; Amalin, Atika Mima; Amalia, Nuke (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
Online learning activities using games or gamified methods make students motivated, capable, and involved to participate in the learning process. There are several gamified platforms that are already available, but there are several obstacles, for example the user takes a long time to compile quizzes and some features in paid gamified so that feature utilization is not optimal. The purpose of this research is to design the user interface and user experience of the gamified platform "Ezedu". Ezedu is a learning media created lecturers and teachers to design educational games easier. The design method uses the User Centered Design (UCD) method. UCD is a term that describes the design process where the end-user will influence how the design is formed. The results of this study are user interface designs that have been adapted to user needs.